Analisis Evaluasi Kurikulum Pembelajaran PAI di SMPN 9 Rejang Lebong (Belitar Muka) - Mohammad Sujud (Lembaga Bale Literasi, 2022)
Curriculum evaluation is carried out to find out how far the implementation of the curriculum has been realized. This research is a field research. The focus of the research is the obstacles to the curriculum in PAI learning at SMPN 9 Rejang Lebong Belitar Muka. The obstacle that arises is the lack of awareness of Muslim teachers in assisting religious programs. Many students have different religious backgrounds, making it difficult to understand religious worship. Inadequate technological facilities in digital-based learning. Lack of collection of Islamic books in the library. The results of the analysis obtained are that the teacher as the executor of the core curriculum needs to increase awareness and competence in learning. Education about religious tolerance needs to be emphasized in the learning process. Education and curriculum must adapt to the times and technology so that learning becomes more effective. Books and a culture of reading are very important in the world of education, schools are responsible for providing the time and place and attracting students' interest to enjoy reading.